(untitled) (Euro-Latin American Journal of Administrative Law, 2014)
The article analyses the issue of good governance and good management of public institutions under the perspective of social control. The issue is examined under the perspective of the fundamental rights of the citizen and human rights, with references to decisions of the Inter-American Court of Human Rights.